2020
DOI: 10.1097/md.0000000000021374
|View full text |Cite|
|
Sign up to set email alerts
|

Gray matter alterations in restless legs syndrome

Abstract: Background: Voxel-based morphometry (VBM) is an objective structural magnetic resonance imaging (MRI) technique which allows researchers to investigate group-level differences in regional gray matter (GM) volume or density over the whole brain. In the last decade, VBM studies in restless leg syndrome (RLS) have exhibited inconsistent and conflicting findings. Methods: Studies will be identified through a computerized literature search of the following databases: PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The current study has several strengths. The most important one is the use of SDM-PSI, an updated CBMA, which has been presented and recommended in several previous studies (Yu et al, 2017 ; Albajes-Eizagirre et al, 2019b ; Sheng et al, 2020a , b ; Wang et al, 2020 ). This technique has made significant methodological improvements to overcome the drawbacks of alternative procedures and produce accurate results (Albajes-Eizagirre et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study has several strengths. The most important one is the use of SDM-PSI, an updated CBMA, which has been presented and recommended in several previous studies (Yu et al, 2017 ; Albajes-Eizagirre et al, 2019b ; Sheng et al, 2020a , b ; Wang et al, 2020 ). This technique has made significant methodological improvements to overcome the drawbacks of alternative procedures and produce accurate results (Albajes-Eizagirre et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…Coordinate-or image-based neuroimaging meta-analyses (CBMA, IBMA) have become increasingly popular approaches that can transcend the limitations of individual single studies by retrospectively synthesizing the findings of the previously published literature (Laird et al, 2009;Müller et al, 2018;Salimi-Khorshidi et al, 2009;Tahmasian et al, 2019). Recently, several coordinate-based metaanalyses on sleep deprivation (Javaheripour et al, 2019;Ma et al, 2015;Saletin et al, 2019), insomnia disorder (Jiang et al, 2020;Wu et al, 2020), obstructive sleep apnea (OSA; Huang et al, 2019;Shi et al, 2017;Tahmasian et al, 2016;Weng et al, 2014), narcolepsy (Weng et al, 2015) and restless legs syndrome (RLS; Sheng et al, 2020) reported converging regional brain abnormalities across available original studies. However, the findings of these meta-analyses are also divergent because of their heterogeneity in search strategies, included samples and analysis flexibility (Müller et al, 2018;Tahmasian et al, 2019).…”
Section: Why Is An Internati Onal Coll Abor Ation Needed?mentioning
confidence: 99%
“…Coordinate-based meta-analyses (CBMA) are significant and powerful tools to assess brain abnormalities in voxel-based neuroimaging studies ( 25 , 26 ). The techniques for CBMA have been evolving and applied in recent years ( 27 , 28 ). Seed-based d mapping with permutation of subject images (SDM-PSI), the latest generation of the CBMA method, allows a familywise error (FWE) correction for multiple comparisons of the results, which improves statistical efficiency ( 29 ).…”
Section: Introductionmentioning
confidence: 99%